Effects of Socio-economic, Demographic and Internet Exposure Factors on School Performance among Selected Students of Nilkhet High School (Bangladesh Journal of Nutrition, 2013)
A cross sectional study was carried out to investigate the effects of socio-economic, demographic and internet exposure factors on school performance among 10 grade students of Nilkhet High School. All of the eighty seven students were selected for this study. In this study school performance was measured by class roll number. The lower the class roll number the better the school performance. During Chi-square test grade (A+, A, A-, B, C, D) achieved in the class 9 final examination was taken as dependent variable. An upper grade indicates better school performance than lower grade. Class roll number were highly negatively correlated with the factors-actual income of the family, actual monthly tuition cost, number of rooms in the house, number of earning persons in the family, and this correlation was significant (p